The use of Astragalus membranaceus as an eco-friendly alternative for antibiotics in diets of Japanese quail breeders - Mahmoud Alagawany; Mayada R. Farag; Mohammed A. Al-Harthi; Khalid A. Asiry; Fulvia Bovera; Youssef A. Attia (Poultry Science, 2023)
ABSTRACT: Mature Japanese quails (n. 180), aged 8 wk, were divided into 6 groups to evaluate the influence of dietary Astragalus membranaceus powder on laying and reproductive performances, quality of egg, and blood metabolites. A completely randomized design experiment was performed including 6 groups. The first group of quails was served as control (basal diet). While, the 2nd, 3rd, 4th, 5th, and 6th group of quails fed a basal diet supplemented with 1, 2, 3, 4, and 5 g of AM powder/kg diet, respectively. Egg number (EN), weight (EW), and mass (EM) were not significantly influenced by dietary Astragalus membranaceus at all tested levels. The hatchability percentage was quadratically improved by dietary supplementation of A. membranaceus. Dietary supplementation of A. membranaceus positively affects (linear and quadratic) liver and kidney functions. Plasma total cholesterol (TC; P < 0.001) and Triglyceride (TG; P < 0.001) were linearly and quadratically decreased by dietary A. membranaceus increasing level. Blood urea level decreased with increasing A. membranaceus levels in the quail diet. The immunoglobulin G (IgG) and M (IgM) were higher than the control at all A. membranaceus levels. In conclusion, feeding quail breeders with Astragalus membranaceus at 1 g/kg diet has beneficial effects on feed conversion ratio; on production at 2 g/kg diet; on hatchability and immunity at 5 g/kg diet; and on total cholesterol at 3 g/kg diet and on shell quality at 4 g/kg diet. A. membranaceus products are expected to be novel valuable dietary supplements for poultry production, depending on the target trait.